Integrated Control Sytems of Mycotoxin Contamination - Romsyah Maryam (Indonesian Center for Animal Research and Development, 2006)
Contamination of mycotoxins produced by Aspergillus spp., Fusarium spp . and Penicillium s pp . i n agricultural products has been a concern regarding their effect to health and economic impact. Integrated control system should be based on Hazard Analysis and Critical Control Point (HACCP) approach involving Good Agricultural Practices (GAP) and Good Manufacturing Practices (GMP) . Prevention should be carried out through pre harvest, harvest, post harvest, as well as control quality at all stages of production. Pre harvest control is conducted through the selection of resistant varieties, insect control and weeds management mechanically or applying fungicides and herbicides, plant rotation, irrigation and soil management, as well as biological control . Harvesting at the right time using clean equipments from fungal contamination and insect infestation avoids the contamination of mycotoxins . Post harvest control by physical selection, washing and dilution, drying, storage, application of chemicals and binding agents, natural products, nutrients and vitamins, microbiological control, heating and radiation could also minimize mycotoxin in food and feed . Although chemicals can effectively reduce mycotoxin, the use of those on food/feed should be considered the safety . The addition of natural products, nutrition supplements and vitamins suppress the negative effect of mycotoxin on animals . The use of non-toxigenic fungi and other microbes as biological control is the effective and safe methods for food/feed . The implementation of integrated mycotoxin control system by utilizing the HACCP concept would meet the qualified and safe food/feed products . Key words: Control, mycotoxins, HACCP